Soil bacterial responses to experimental warming and drought across winter wheat growth stages in the North China Plain - Kpalari, Djifa Fidele; Fu, Yuanyuan; Li, Sen; Cao, Hui; Kama, Rakhwe; Hamani, Abdoul Kader Mounkaila; Liu, Junming; Ma, Shoutian; Lv, Dongxue; Gao, Yang (Frontiers in Plant Science, 2025)
IntroductionWhile climate change alters the balance of the terrestrial ecosystems, the impact on the soil bacterial community remains poorly understood. A field experiment was conducted to assess the effects of warming, drought, and their combination on the soil bacterial community at different growth stages of winter wheat.MethodsFour treatments were defined for this study: warming at 1.5°C combined with full irrigation (TWS) and deficit irrigation (TWD), then ambient temperature combined with full irrigation (TNS) and deficit irrigation (TND).ResultsTWS, unlike TND, promoted nitrogen availability for plants and root exudation. The abundance and diversity of the bacterial community were more responsive to different climatic stresses at the jointing stage than at other growth stages. Chloroflexi, Firmicutes, and Bacteroidota were positively correlated with soil inorganic nitrogen, the root total organic carbon (TOC), and negatively correlated with available phosphorus (AP), available potassium (AK), soil organic carbon (SOC) under TND, while an opposite trend was observed with Actinobacteria and Proteobacteria. Furthermore, under TWS, Bacteroidota, unlike Actinobacteria, was positively correlated with NH4+, NO3-, TOC, and negatively correlated with AP, and SOC. The bacterial community network feature values were higher under TWD and lower under TNS.ConclusionThese results indicate that the sensitivity of the rhizosphere bacterial community to the different climatic stresses varies according to the growth stage, and that the community is particularly more responsive at the jointing stage than at the later stages.